Synthesis and Characterization of Flame-Retardant Polyurethane Elastomers Using Phosphorus-Containing Chain Extender - Xu, Wenzong; Li, Wenxiu; Ren, Mingyuan; Yin, Jianguo (Asian Journal of Chemistry, 2013)
Phenylphosphonic diamine was synthesized from phenylphosphonic dichloride and characterized by Fourier transform infrared spectroscopy and nuclear magnetic resonance. Then phenylphosphonic diamine was used to prepare a series of phosphorus containing polyurethane elastomers (PPUEs) with different phosphorus contents. Combustion behaviour and thermal degradation behaviour of the PPUEs and polyurethane elastomer (PUE) were investigated by macroscale combustion calorimetry and thermogravimetric analysis. The macroscale combustion calorimetry result reveals that the value of peak heat release rate and total heat release of PPUEs are lower than those of PUE made by 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA). The TGA result shows that PPUE2 has poorer thermal stability than PUE when they are obtained from the same soft segment, but the char yield of PPUE2 is higher than that of PUE.